Pengaruh Total Asset, Return on Asset, dan Equity to Total Asset Terhadap Utilisasi Credit Line - Rahmat Setiawan (Jurusan Tata Niaga, Politeknik Negeri Lhokseumawe, 2019)
This paper intends to analyze the relationship of these following asset components (Total Assets, Return of Assets (ROA), and Equity to Total Assets) to Credit Line Utilization. Ordinary Least Square is applied as a technique for its data analytical. This research observed 78 data transaction samples which have a performance window taken from 2016 until 2017. The results show there are negative significant relationships between Total Assets, Return of Assets (ROA), and Equity to Total Assets to Credit Line Utilization.